Restorative Justiceand Protection of Children's Rights in the Criminal Legal Process - Egi Kurniawan (PT. Anagata Sembagi Education, 2024)
Protection for children who are in conflict with the law in the juvenile criminal justice process, from investigation, prosecution, court, to juvenile correctional facilities, has not been able to provide protection that provides a sense of justice for children. In fact, children's rights are often ignored. In the case of children, children can be perpetrators, victims, or witnesses, so serious protection and treatment is needed to prevent wider and detrimental impacts on them. Handling of children's cases must be carried out by officials who understand children's problems. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System marks progress in protecting children in conflict with the law, by changing the paradigm in handling these cases. The process of resolving children's cases is not only limited to the judiciary, but can also be carried out outside the judiciary through diversion with a restorative justice approach. This approach involves all relevant parties, including perpetrators, victims, witnesses and other parties, to jointly find solutions in the best interests of the child.